2005
DOI: 10.1080/10641950500281100
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Resolution of Preeclamptic Symptoms After Intrauterine Death of One Twin

Abstract: In a 34 year old woman with dichorionic twin pregnancy preeclampsia resolved after the intrauterine death of one of the HLA-identical twins and recurred with the growth of the placenta of the surviving twin later in pregnancy. This case gives indirect evidence that the clinical course of preeclampsia is a dose-dependent phenomenon in conjunction with vital placental tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Other authors reported periods of time ranging from 1 to 3 weeks for resolution of various features of pre-eclampsia. 1,3,4,7 Umbilical artery flow abnormalities are also usually persistent or progressive, and our case is also the first instance in which flow in the umbilical artery has been shown to improve after the demise of one twin. Absent end diastolic flow in Twin A, which developed before the demise of Twin B, persisted for 1 month after the demise of Twin B and then there was a return of end diastolic flow.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Other authors reported periods of time ranging from 1 to 3 weeks for resolution of various features of pre-eclampsia. 1,3,4,7 Umbilical artery flow abnormalities are also usually persistent or progressive, and our case is also the first instance in which flow in the umbilical artery has been shown to improve after the demise of one twin. Absent end diastolic flow in Twin A, which developed before the demise of Twin B, persisted for 1 month after the demise of Twin B and then there was a return of end diastolic flow.…”
Section: Discussionmentioning
confidence: 54%
“…In most of the reported cases, the twin that died in utero was growth-restricted. [1][2][3][4] In the case reported by van der Houwen et al, 4 the twin that died was growth-restricted due to triploidy. As pre-eclampsia in some dichorionic twin gestations may be linked to the poor growth of one fetus, some authors have described selective feticide of the abnormal twin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually preeclampsia progresses without any recovery until birth. Few cases of resolution of preeclampsia after spontaneous intrauterine death of one twin or selective termination of a dichorionic pregnancy have been reported ( 1 , 6 , 7 ) . Narasimhulu et al ( 8 ) reported resolution of superimposed preeclampsia in a surviving fetus after the intrauterine demise of its co-twin and suggested that placental involution after fetal demise was the key to resolution of preeclampsia (resolution period take 1 to 3 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Preeclampsia originates from the placenta, and its progressive clinical course is only treated by delivery of the placenta ( 1 ) . The incidence of disease is 3-5% and it is known as a major cause of maternal and perinatal mortality ( 2 ) .…”
Section: Introductionmentioning
confidence: 99%